Intervening effect of personal value on the code of ethics to ethical judgment - Yuli Anwar (STIE Binaniaga, 2020)
The purpose of this study is to examine and analyze empirically the effect of code of ethics understanding to ethical judgment through personal value of public accountant. The model proposed in this research was tested by means of structural equation modeling. The data were collected from purposive sampling and the number of samples of this research were 301 partners, manager, supervisor, and senior accountant in Indonesia. Construct that directly affect each other in this study are code of ethic to personal values and code of ethic to ethical judgment and and prove that personal value is an intervening variable. The model proposed in the research shows the impact code of ethics, personal value and ethical judgment. Future research should study of morality of auditor and collected sample from Asian countries. Partner, manager, supervisor, and senior auditor may take a decision wiser with ethical judgment with based on fact. The model proposed in this research partner, manager, supervisor, and senior auditor have positive direct impact of each code of ethic to personal values and positive direct impact code of ethic to ethical judgment. Keywords: Code of Ethics, Personal Value, Ethical Judgment